China’s drug clinical trial institution record-keeping system: Qualification requirements for PI are the key - Huang, Nanqu; Huang, Wendi; Luo, Yong; Huang, Juan (Frontiers in Pharmacology, 2023)
It has been three years since China implemented new management regulations for drug clinical trial institutions in December 2019, the most important of which is to change the qualification recognition of drug clinical trial institutions into record-keeping system. The original intention of the institution record-keeping system was to solve the shortage of clinical trial resources in China, effectively expand the number of clinical trial institutions, and effectively alleviate the contradiction between medical treatment and scientific research. After implementing the record-keeping system, although these goals have been achieved to a certain extent, there are still areas worthy of optimization and improvement. Therefore, we evaluated the new process, in particular the requirements, in order to see what possible barriers in the record-keeping system of institutions. We find that the requirements for principal investigator (PI) qualifications are the key to the record-keeping system. This reflects the shift of Chinese regulators' supervision of clinical trials to supervision of the ability to conduct clinical trials. However, the ambiguity of the definition of PI qualification has hindered implementation of the record-keeping system and reduced the release of clinical trial resources.